ChemInform Abstract: Magnesium Double Nitride Mg3GaN3 as New Host Lattice for Eu2+ Doping: Synthesis, Structural Studies, Luminescence, and Band‐Gap Determination. Issue 2 (14th January 2014) - Hintze, Frauke; Johnson, Neil W.; Seibald, Markus; Muir, David; Moewes, Alexander; Schnick, Wolfgang
Abstract Eu‐doped Mg3GaN3 (I) and binary nitride Mg3N2 (II) are prepared by reaction of the corresponding metals with NaN3 in a sodium flux (welded Ta ampules, 760 °C, 2 d; cooling to 200 °C with a rate of 0.06 °C/min).